Błażej Stolarski. Droga do awansu cywilizacyjnego chłopa polskiego w latach 1900-1918 - Perzyna, Paweł (Acta Universitatis Lodziensis. Folia Historica, 1997)
Błażej Stolarski’s social rise linked with economic and social changes which took place at the beginning of the XXth century. In consequence of his self-education as well as a wide-spread educational, cultural and economic action of the national movement on the country areas of the Kingdom of Poland, Stolarski became aware of necessity of an intensification in agriculture. Stolarski’s activity in the Agricultural Circles (since 1907), the most important social and economic organization of peasants in the Kingdom of Poland, as well as a process of social democratization made it possible for him to enter political activity. In 1912 he became a co-founder of Narodowy Związek Chłopski (The National League of Peasants). In 1915 Polskie Stronnictwo Ludowe PSL (Polish Peasants’ Party), which united 3 political organizations of peasants, designated B. Stolarski to Centralny Komitet Narodowy (Central National Committee), being a representation of the independence parties of the Kingdom of Poland. The most successful for Stolarski’s own political career was 1917. He became a member of Tymczasowa Rada Stanu (Provisional State Council) and a chairman of PSL then. In November 1918 B. Stolarski entered into the Provisional People’s Government of the Republic of Poland in Lublin and signed it’s programm declaration. Stolarski devoted himself to a development of an educational system in Będków district. In 1914 he founded a school in Shigocice and 3 years later he became a co-founder and a chairman of a society for establishing a secondary school in Będków.